Effect of Part Replacement of Mercaptobenzothiazole with Locust Bean Cake on the Thermal and Electrical Conductivities of Natural Rubber Vulcanizates (Biological Sciences - PJSIR, 2005)
The effect of part replacement of mercaptobenzothiazole (MBTS) with locust bean cake (LBC) on the thermo- dynamic parameters, thermal and electrical conductivities of natural rubber (NR) composite, was examined. Generally, all the thermodynamic parameters, the thermal conductivity and the electrical conductivity of the NR vulcanizates were altered on the inclusion of the MBTS/LBC mix in the formulations of the composites. The degree of alteration of these properties increased with increasing LBC contents in the MBTS/LBC mix. It appears that upto 50/50, MBTS/LBC mix, the lower the entropy change of the molecules of the composite, the higher was the crosslink density of the composite, and the better was the ability of the composite to conduct heat and electricity. It is, therefore, advantageous to replace MBTS with LBC upto 50% in the formulations of NR composites for improved thermal and electrical insulation.